Services of Peerzada Imdad Hussain in Promotion of Religion: A Review: فروغ علم دین میں پیرزادہ امداد حسین کی خدمات : ایک جائزہ - Irfan, Hafiz Muhammad; Rizwan, Dr. Muhammad (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2021)
Peerzada Imdad Husain is a famous religious scholar in United Kingdom. He did a lot efforts for the propagation of Islam in United Kingdom especially and in whole Europe. He wrote many famous books about Fiqa , Hadith and on other ironical topics. He also wrote a commentary of Holy Quran known as “Tafseer Imdad ul Karam”. This article discusses about his efforts and work about Islam and especially his efforts for the propagation of religious knowledge. In the article, his famous books are analyzed. Furthermore, his others services are discussed in detail. This article shows his keenness and relation with religious knowledge.